Evaluation of Online Learning Satisfaction During Pandemic Using the IPA-Kano Method - Ismianti, Ismianti; Mastrisiswadi , Hasan; Wahyu Adventari Wibowo, Astrid (TALENTA Publisher, 2023)
The COVID-19 pandemic has impacted all aspects of life, including teaching and learning activities. Therefore, the entire community must be ready to do online learning, which will have different processes and results from normal learning. This study aims to determine the level of student satisfaction in online learning during the pandemic. This study uses attributes on Webqual 4.0 and processed using the integration of IPA and Kano. Based on the results of research conducted on 194 respondents, it was found that attributes US1 and IT4 were in the Beginning jewelry category, IT7 attributes were in the Defenseless Strategy point category, IT2 attributes were in the Fatal category, attributes IF1, IF2, IT3 was in the Major weapon category, attributes IF4, IF5 are included in the precious treasure category, and other attributes are included in the removed category because they have the Kano Indifferent category.